A Penalty Technique for Nonlinear Complementarity Problems (Journal of Computational Mathematics, 1998)
In this paper, we first give a new equivalent optimization form to nonlinear complementarity problems and then establish a damped Newton method in which penalty technique is used. The subproblems of the method are lower-dimensional linear complementarity problems. We prove that the algorithm converges globally for strongly monotone complementarity problems. Under certain conditions, the method possesses quadratic convergence. Few numerical results are also reported.
Keywords: Optimization; nonlinear complementarity.